Plastic stents are more cost-effective than lumen-apposing metal stents in management of pancreatic pseudocysts - Chen, Yen-I; Khashab, Mouen A.; Adam, Viviane; Bai, Ge; Singh, Vikesh K.; Bukhari, Majidah; Brewer Gutierrez, Olaya; Elmunzer, B. Joseph; Moran, Robert A.; Fayad, Lea; El Zein, Mohamad; Kumbhari, Vivek; Repici, Alessandro; Barkun, Alan N. (Endoscopy International Open, 2018)
Background and study aims Endoscopic ultrasound-guided drainage is an effective and accepted primary modality for management of pancreatic pseudocyst (PP). A lumen-apposing metal stent (LAMS) has recently been developed specifically for drainage of pancreatic fluid collections which may be superior to using traditional plastic stents (PS) but is more expensive. Because use of a stent involves a risk of unplanned endoscopy, percutaneous drainage (PCD) and surgery, their costs should also be included in the comparison and a cost-effectiveness analysis of LAMS and PS should therefore be performed Patients and methods A decision tree was developed assessing both endoscopic drainage strategies for patients with PP: LAMS and PS over a 6-month time horizon. For each strategy, inpatients received a stent and were followed for subsequent need for direct further interventions or adverse events leading to unplanned endoscopy, PCD, surgery, or successful endoscopic drainage using probabilities obtained from the literature. The unit of effectiveness was successful endoscopic drainage without need for PCD or surgery. Sensitivity analyses were performed. Results Success rates were 93.9 % for LAMS and 96.96 % for PS. Respective costs per successful drainage were US $ 18,129 (LAMS) and US $ 10,403 (PS). The LAMS strategy was thus characterized as dominated by the PS approach because it was costlier and less effective than PS. Both deterministic and probabilistic sensitivity analyses confirmed the robustness of these findings. Conclusion Use of LAMS is not less effective and more costly than PS in management of patients with PP. As such, PS should be preferred over LAMS as initial management of these patients.